Trazabilidad de la producción y composición química del aceite de Aniba rosaeodora Ducke “Palo de Rosa” procedente de plantaciones de la localidad de Tamshiyacu Loreto Perú - Soplin Trigoso, Hilda (2025)
In order to obtain information on the journey of the forest species “rosewood” from established plantations, transportation, primary processing and storage to national and international end users. Based on this information, we can verify that the raw material comes from legal sources for the proper sustainable use of forest resources. The execution of this work is proposed. The purpose is to define the ability to follow the origin, production and chemical composition of the essential oil from Aniba rosodora Ducke, known as “rosewood”. The activities in the field were carried out in crops located in the Tamshiyacu area, while the processing of the raw material to extract the essential oil took place in the initial processing plant of Essential Oils Peru Sac, located in the city of Iquitos, in the Loreto region, Peru. The information on the entire administrative process to obtain plantation records and oil analysis were also obtained from the same company. The extraction process of the raw material was established in situ, which includes stem, branches, twigs and leaves, to later establish the weight ratio between them, constituting 65.1% stem, 14.3% primary branches, 13.4% twigs and 7.2% leaves, which makes it different from other forest species since the essential oil is obtained from all of these. The oil yield is established based on the parts used, achieving 2% of the leaves, 2.3% of the secondary branches and 3.1% of the stem and primary branches. The quality of the essential oil depends on one of the main components, linalool, whose percentage according to the analysis sources is between 78.21 and 83.26%, whose values are above the minimum required by importing companies.